The Role of Job Satisfaction in Increasing Productivity trainers at Vocational and Business Skills Training Centers in Khartoum State (Karari Center Model) - Elsaeed, Hoyam Mahgoub Mohammed; Mohammed, Bakhita Mohammedzain Ali; Ahmed, Ali Farah (Journal of Ecohumanism, 2025)
The study applied to know the criteria of Incentive finance for the trainers in vocational training Centre and business skills in Khartoum state.Also to fiquer out the difference between productivity and incentive finance for trainers in Vocational training center and business skills in Khartoum state.And to know the incentive finance difference between trainers in Vocational training center,according to variability of salary and the incentive finance (wages).Beside, to know the impact of directions for trainers in Vocational training center.The study applied discriptive analytical method for trainers at Vocational training center Khartoum-state.The researcher usr Questionnair and the sample of study was taken randomly from the population.The researcher distributed (200) Questionnair for the study population and it was accepted from all the total numbers no exception was done for the Questionnair validity which it led the total number (200).The study finding and results as follows:There was unacceptably of salary for the trainers at the Vocational training center Khartoum- state and had resulted in workers' performance.Also there was an obvious weakeness in salary payment that offer for trainers,and it indicted the unacceptability of salary system in training center.There was a consistency shows that incentive finance and good salary encourage effective working.The study recommendation: improving salary payment and the incentive finance system to achieve accebtailty in work which will result in performance and productivity.Laying basic and specific critira for offering salary payment which will achieve justice between workers .Improve work environment. Designing safety occupational procedures perfectly.Give trainers a participations to make decisions and offer workers trust to excuse work better.